SGMS2 in primary osteoporosis with facial nerve palsy - Pihlström, Sandra; Richardt, Sampo; Määttä, Kirsi; Pekkinen, Minna; Olkkonen, Vesa M.; Mäkitie, Outi; Mäkitie, Riikka E. (Frontiers in Endocrinology, 2023)
Pathogenic heterozygous variants in SGMS2 cause a rare monogenic form of osteoporosis known as calvarial doughnut lesions with bone fragility (CDL). The clinical presentations of SGMS2-related bone pathology range from childhood-onset osteoporosis with low bone mineral density and sclerotic doughnut-shaped lesions in the skull to a severe spondylometaphyseal dysplasia with neonatal fractures, long-bone deformities, and short stature. In addition, neurological manifestations occur in some patients. SGMS2 encodes sphingomyelin synthase 2 (SMS2), an enzyme involved in the production of sphingomyelin (SM). This review describes the biochemical structure of SM, SM metabolism, and their molecular actions in skeletal and neural tissue. We postulate how disrupted SM gradient can influence bone formation and how animal models may facilitate a better understanding of SGMS2-related osteoporosis.